186k views
3 votes
The y-intercept of 2x - y = 6 is -6.
O False
True

User Seumasmac
by
4.7k points

2 Answers

1 vote

Answer:

true

Explanation:

you switch the 2x to the other side to get -y = 2x + 6

then you multiply everything by -1 to get y = -2x-6

-6 is the y int

User Alfred Fuller
by
5.4k points
3 votes

Answer:

It is true

Explanation:

Convert to slope-intercept form:

2x-y=6

-y=6-2x

y=-6+2x

y=2x-6

Since y=mx+b is the form we want, then b=-6, making the statement true.

User KamikazeCZ
by
5.3k points